Searching the analogue 2p₃/₂-resonance in the ³⁶S(p,γ)³⁷Cl reaction - Vodin, A.N.; Ushakov, I.V.; Kachan, A.S.; Korda, L.P.; Mischenko, V.M.; Nemashkalo, B.A. (Вопросы атомной науки и техники, 2002)
Searching the analogue 2p₃/₂-resonance in ³⁷Cl, which is an isobaric analogue of the parent level with E* = 0.646 MeV (Jp = 3/2-) of ³⁷S was carried out. The excitation function for the ³⁶S(p,g)³⁷Cl reaction was measured in the energy region Ep = 2487 - 2680 keV. Resonance strengths were determined for 44 resonances. The decay schemes and branching ratios of four resonances were investigated at Ep = 2539, 2599, 2659 and 2676 keV. Spins and parities of these resonances (3/2⁺, 3/2⁺, 3/2⁺ and 5/2⁺, correspondingly) were established from angular distributions of γ-rays and measured intensities of γ-transitions.